Java-Based Goods Data Recording Application System at Achfi Balamoa Store - Wicaksono, Aji (Interdisciplinary Social Studies, 2022)
Background: The use of information technology applied through information systems provides convenience to users, especially shop owners in doing work, not only in the recording of goods but also in the creation of goods data reports. Goods data is an important element in a store that must be managed properly and requires thoroughness so that applications are needed to minimize errors. Aim: It makes it easier the process of recording data of goods that previously still use manual systems. Method: In researching making application systems, the method used is a qualitative method, where the information obtained is sourced from various collections of data analysis and existing theories and then conclusions are drawn to obtain new theories. Findings: The result of this application system is that the collection of goods will be faster and reports of the entry and exit of goods more accurate. The research method used is a qualitative method, where the information obtained is sourced from various data analysis sets and existing theories and then concluded to get a new theory.